PROCEEDING ARTICLE TEMPLATES 3RD ICTESS (THE EFFECTIVENESS OF ISLAMIC COOPERATION ORGANIZATIONS (OIC) IN HANDLING THE PALESTINEISRAEL CONFLICT IN 2016-2019) - Lestari, Atik; Widhiyoga, Ganjar; Dipo Kusumo, GPH (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research discusses the effectiveness of Islamic cooperation organizations (OKI) in dealing with the 2016 Palestinian-Israeli conflict -2019. Palestine and Israel are two countries in the Middle East which are still in conflict until now. This conflict occurs because of three things, namely, the establishment of the independent state of Israel in 1948 in the Palestinian territories, until now Israel continues to annex the Palestinian territories and Israel does not comply with UN resolution No. 181 dated 29 November 1947 concerning the division of Palestinian and Israeli territories, and the third is regarding the transfer of the Israeli capital from Tel Aviv to Jerusalem which was previously the capital of Palestine. Responding to this, the Islamic Cooperation Organization (OIC), which has members from Islamic countries and the majority of the Muslim population, issued various resolutions. This study was analyzed using the theory of international regime effectiveness with a knowledge approach or the Kantian model. The research method used in this study is a qualitative research method with primary and secondary data collection sources. The research was conducted through document collection with descriptive elaboration. This research concludes that the OIC's involvement in dealing with the Palestinian-Israeli conflict has not brought effective results or is not in accordance with what is stated in the OIC Charter (OIC Charter). Keywords: Effectiveness, Organization of Islamic Cooperation, Palestinian Israeli Conflict, Resolution